ANALISIS KESALAHAN BERBAHASA ASPEK EJAAN PADA KUMPULAN CERPEN KARYA SISWA SMP IT NURUL ISLAH - Ambar, Ambar Nur Hidayah; Citra Mutiara Sahni; Ditha Prismasari; Chafit Ulya (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2021)
This study aims to classify and explain the spelling aspects of a collection of shortstories by students of SMP IT Nurul Islah. The object of research, namely the analysis of spellingerrors in a collection of short stories by students of SMP IT Nurul Islah.The method used in this research is descriptive analysis method. The analysis in thisstudy is based on PUEBI. The error aspects analyzed include the use of capital letters, the use ofpronouns, the use of conjunctions, the use of prepositions, the use of loan words, and the use ofpunctuation marks.The number of errors in short stories written by students is as follows: 16 errors in theuse of capital letters, 5 errors in the use of pronouns, 15 uses of conjunctions, 15 uses ofprepositions, 2 uses of absorption words, and 11 uses of punctuation marks.